Carcass, Organ and Organoleptic Characteristics of Spent Layers Fed Bambara Nut Sievates - Ugwu, S.O.C.; Onyimonyi, A.E. (International Journal of Poultry Science, 2007)
The carcass, organ and organoleptic characteristics of spent layers fed Bambara nut sievates (BNS) were investigated. Ninety laying hens of the Brown Nera strain in their 9th week of lay were randomly assigned to five dietary treatment in which BNS were incorporated at levels of 0 (control), 5, 10, 15 and 20 percent. There were eighteen birds per treatment and each treatment was replicated thrice in a Completely Randomized Design. The feeding trial lasted for 45 weeks during which each bird received 120g of feed/day. Results showed that final body weight, dressing percentage and residual weight were significantly affected by treatments (P<0.05). There was an observed increase in these parameters up to the 10 percent levels after which the values declined. Birds on the 10 percent BNS diets were superior in these parameters. Gizzard and liver weights increased significantly (P<0.05) as levels of BNS increased. Organoleptic investigations revealed that colour, taste and texture of the breasts muscle were significantly (P<0.05) affected by treatments. Birds on the 10 percent BNS diet had significantly higher colour value whereas taste and texture significantly increased as level of BNS in the diets increased. In conclusion, the results of this study reveal that BNS can be incorporated at 10 percent level in diet of laying hens without compromising carcass characteristics at end of lay.